2019
DOI: 10.15305/ijrci/v7i1/323
|View full text |Cite
|
Sign up to set email alerts
|

Precision and diagnostic accuracy verification of VITROS HIV combo assay

Abstract: Background/Objective: NACO has laid down three structured algorithms (I, II, III) for HIV screen, surveillance and diagnosis. It is the responsibility of the laboratories to select, verify and evaluate the methods fitting into the algorithm of HIV testing. The present study has attempted to evaluate VITROS® HIV combo assay through comparison with Abbott Architect HIV combo assay. Method:The study evaluated VITROS® HIV combo assay through precision verification and diagnostic accuracy assessment by adopting CLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Raanathan et al . [ 13 ] evaluated VITROS HIV Combo assay through precision verification and diagnostic accuracy assessment by adopting CLSI guidelines and reported that the repeatability CV% cerebrovascular reactivity of 2.35% and within lab CV% (CVWL) of 3.77% was well within the manufacturer’s claim (σR-3%, σWL-4.8%) and was found to be within acceptable limits.…”
Section: Discussionmentioning
confidence: 99%
“…Raanathan et al . [ 13 ] evaluated VITROS HIV Combo assay through precision verification and diagnostic accuracy assessment by adopting CLSI guidelines and reported that the repeatability CV% cerebrovascular reactivity of 2.35% and within lab CV% (CVWL) of 3.77% was well within the manufacturer’s claim (σR-3%, σWL-4.8%) and was found to be within acceptable limits.…”
Section: Discussionmentioning
confidence: 99%